Boosting the oral bioavailability of anticancer drugs through intentional drug–drug interactions. (28th June 2021) - Eisenmann, Eric D.; Talebi, Zahra; Sparreboom, Alex; Baker, Sharyn D.
Abstract: Oral anticancer drugs suffer from significant variability in pharmacokinetics and pharmacodynamics partially due to limited bioavailability. The limited bioavailability of anticancer drugs is due to both pharmaceutical limitations and physiological barriers. Pharmacokinetic boosting is a strategy to enhance the oral bioavailability of a therapeutic drug by inhibiting physiological barriers through an intentional drug–drug interaction (DDI). This type of strategy has proven effective across several therapeutic indications including anticancer treatment. Pharmacokinetic boosting could improve anticancer drugs lacking or with otherwise unacceptable oral formulations through logistic, economic, pharmacodynamic and pharmacokinetic benefits. Despite these benefits, pharmacokinetic boosting strategies could result in unintended DDIs and are only likely to benefit a limited number of targets. Highlighting this concern, pharmacokinetic boosting has mixed results depending on the boosted drug. While pharmacokinetic boosting did not significantly improve certain drugs, it has resulted in the commercial approval of boosted oral formulations for other drugs. Pharmacokinetic boosting to improve oral anticancer therapy is an expanding area of research that is likely to improve treatment options for cancer patients.